Prevention of biliary fistula after partial hepatectomy by transcystic biliary drainage: randomized clinical trial. Issue 7 (9th January 2020) - Maulat, C; Regimbeau, J-M; Buc, E; Boleslawski, E; Belghiti, J; Hardwigsen, J; Vibert, E; Delpero, J-R; Tournay, E; Arnaud, C; Suc, B; Pessaux, P; et al.
Abstract: Background: Biliary fistula is one of the most common complications after hepatectomy. This study evaluated the effect of transcystic biliary drainage during hepatectomy on the occurrence of postoperative biliary fistula. Methods: This multicentre RCT was carried out from 2009 to 2016 in nine centres. Patients were randomized to transcystic biliary drainage or no transcystic drainage (control). Patients underwent hepatectomy (more than 2 segments) of non-cirrhotic livers. The primary endpoint was the occurrence of biliary fistula after surgery. Secondary endpoints were morbidity, postoperative mortality, duration of hospital stay, reoperation, readmission to hospital, and complications caused by catheters. Intention-to-treat and per-protocol analyses were performed. Results: A total of 310 patients were randomized. In intention-to-treat analysis, there were 158 patients in the transcystic group and 149 in the control group. Seven patients were removed from the per-protocol analysis owing to protocol deviations. The biliary fistula rate was 5·9 per cent in intention-to-treat and 6·0 per cent in per-protocol analyses. The rate was similar in the transcystic and control groups (5·7 versus 6·0 per cent; P = 1·000). There were no differences in terms of morbidity (49·4 versus 46·3 per cent; P = 0·731), mortality (2·5 versus 4·7 per cent; P = 0·367) and reoperations (4·4 versus 10·1 per cent; P = 1·000). Median duration of hospital stay was longer in the transcystic group (11 versus 10 days; P = 0·042). The biliary fistula risk was associated with the width and length of the hepatic cut surface. Conclusion: This randomized trial did not demonstrate superiority of transcystic drainage during hepatectomy in preventing biliary fistula. The use of transcystic drainage during hepatectomy to prevent postoperative biliary fistula is not recommended. Registration number: NCT01469442 ( http://www.clinicaltrials.gov ). Graphical Abstract: This RCT evaluated the effect of biliary drainage with a transcystic catheter during hepatectomy on the occurrence of postoperative biliary fistula. A total of 310 patients were randomized in nine centres; the analysis included 158 patients in the transcystic group and 149 in the control group. The biliary fistula rate was similar in the transcystic and control groups. Therefore, the use of transcystic drainage during hepatectomy to prevent postoperative biliary fistula is not recommended. Biliary drainage not of added value